Life prediction by ferrite–pearlite microstructural simulation of short fatigue cracks at high temperature - Wang, Lu; Wang, Zheng; Zhao, Jie (International journal of fatigue, 2015)
•The short crack’s fatigue behavior was simulated based on Monte Carlo method.•The material’s microstructure was modeled by correctional Voronoi-polygons.•Basal energy was introduced to present the microstructure’s inherent energy to cracking.•The energy increment was introduced to simulate the driving force.•The simulation results have a satisfying agreement with the experimental ones. This paper dealt with fatigue behavior simulation based on ferrite–pearlite microstructure modeled by correctional Voronoi-polygons. The model took grain size, grain orientation and the percentage of pearlite and ferrite into consideration. The basal energy was proposed to represent the inherent energy for slip-band and grain boundary to cracking. The driving force for crack initiation and propagation caused by load condition was considered as the energy increment of slip-band and grain boundary. The fatigue behavior including crack initiation, propagation, coalescence and interference were simulated based on Monte Carlo method. The simulation results show a satisfying agreement with the experimental ones.